Colaboración con el SENA en el desarrollo de videojuegos usando tecnología de captura de movimiento (2016)
Video capture devices are tools used to facilitate and speed up animation work for the development of film, television, and video game projects, among other projects that use digital media. This technology tends to be out of the question for many projects of small or medium importance, whether it be for reasons of cost, implementation, or technical training. It is with a particular focus on addressing these difficulties that the Tecnoparques of SENA (National Learning Service) offer their equipment to companies and educational institutions, in addition to providing personnel trained in its operation and management.Many companies that get involved in areas of digital media such video games can see themselves as greatly benefiting from a collaboration with SENA. The problems lies, first of all, in the lack of knowledge that many companies have regarding the support initiatives that the government in general, and that SENA in particular, offer to domestic companies in this sector. Additionally, many of the companies interested in undertaking a collaborative project, not only with SENA but with any other company, have neither the means nor the knowledge to design, manage, and execute a project of a collaborative nature with a similar entity. With the goal of proposing a solution to these problems, a work strategy is now presented which allows us to organize access to the resources offered by SENA, coordinate the different work teams that can appear to be involved and execute a collaborative projectthat is successful both for SENA and the institutions involved. Results of a small test project carried out using the proposed guidelines are also presented.